(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The challenges of digital transformation encourage the search for approaches to measure the impact of digital technologies that are increasingly used in the service sector on the quality of population life. The existing methods of assessing the impact of certain factors on the quality of life, including sample observations and surveys, the calculation of various indicators and indices, the construction on this basis of international ratings that give an idea of the readiness of the national economy as a whole and the service sector as its most important segment, to digital transformation. The article proves that the transition from spontaneous to targeted implementation of digital transformation should take into account how the specific features of traditional services change.